Influence of irrigation and gypsum on wheat cultivation in saline soil - Mamun, Abdullah Al; Sarker, Protima Rani; Noor, Md Mahmud Al (Research in Agriculture Livestock and Fisheries, 2019)
Irrigation application and organic amendments could contribute to the improvement of wheat production in coastal areas. Field experiment was carried out at Shamnagar, Satkhira Sadar for the improvement of wheat production in saline areas through irrigation application and gypsum amendments. Two wheat cultivars viz. L-880-43 and BARIghom- 26 were used as test crops. There were six treatments such as control (no irrigation); one irrigation at vegetative stage with canal water (canal water means rainwater harvested in natural/man-made canal); one irrigation at vegetative stage with STW water + Gypsum application @ 200 Kg/ha (STW means sallow tube-well); Irrigation at vegetative and heading/flowering stage with canal water; Irrigation at vegetative stage with saline canal water + Gypsum application @ 200 Kg/ha; Irrigation at vegetative and heading/flowering stage with STW water + Gypsum application @ 200 Kg/ha. The treatments were allocated in the main-plot and the cultivars in the sub-plot all experimental plots received recommended doses of urea, triple super phosphate, and muriate of potash. The treatments were imposed accordingly. The results showed that soil salinity caused a significant reduction in growth and yield components of both wheat cultivars. Irrigation application and Gypsum amendments significantly increased the growth and yield components of both cultivars under soil salinity. Soil salinity also reduced grain yields of both cultivars. Combined application of irrigation water and gypsum amendments showed higher yields than that of sole application of irrigation water during saline conditions. Gypsum used as amendments because it reduces the soil salinity. Therefore, the present study suggests that wheat production might be feasible in coastal areas of southern Bangladesh (saline soils) through irrigation application and gypsum amendments. Res. Agric., Livest. Fish.6(1): 1-10, April 2019